Intense connection and love: The experiences of autistic mothers. (October 2021) - Dugdale, Amber-Sophie; Thompson, Andrew R; Leedham, Alexandra; Beail, Nigel; Freeth, Megan
Knowledge of how parenthood is experienced by autistic women is currently poor. Nine autistic mothers to children aged 5–15 years completed semi-structured interviews, analysed using Interpretative Phenomenological Analysis. All mothers considered at least one of their children to also be autistic. Four superordinate themes emerged: 1. Autism fundamentally impacts parenting ; 2. Battle for the right support ; 3. Development and acceptance ; and 4. The ups and downs of parenting . The themes demonstrate that while motherhood is largely a joyful experience for autistic mothers (Themes 1 and 4), it is associated with specific issues unlikely to be found in neurotypical motherhood (Theme 1), including negotiating misunderstandings from others (Theme 2). The need for self-care and self-acceptance was expressed (Theme 3) with parenting resulting in personal growth and adaptation (Theme 3). Feelings of intense connection and closeness were experienced (Theme 4), though managing children's needs had a profound personal impact (Themes 2 and 4). The findings demonstrate that service-providers would benefit from training, ideally led by autistic individuals, on how autism presents in adulthood, masking, the potential for mismatching between emotional experience and facial expression, sensory needs (especially in pregnancy), and the double empathy problem (Theme 2). This study represents the first systematic in-depth analysis of the experiences of autistic mothers presented from their own perspectives. Lay abstract: For many women, adulthood involves becoming a mother. Knowledge of how motherhood is experienced by autistic women is currently poor. Poor knowledge has a range of negative consequences and can lead to inappropriate support. In this study, nine autistic women were interviewed about their experiences of motherhood. Seven of the nine mothers had an officially diagnosed autistic child, the final two mothers also suspected at least one of their children to be autistic. Systematic in-depth analysis of interview transcripts identified a range of common themes. Participants largely experienced motherhood as joyful, rewarding, and enjoyable, though managing children's needs had a profound personal impact. Participants reflected on the need for self-care and self-acceptance, resulting in personal growth and adaptation. Participants also spoke of strong bonds, feelings of intense connection, and a range of shared experiences with their children. It was also clear that autistic motherhood is associated with a series of challenges unlikely to be experienced by non-autistic mothers, including the necessity of negotiating misunderstandings from others. The findings demonstrate that, generally, professionals need to be better educated on how autism presents in adulthood, including the fact that autistic women often engage in behaviour to mask their true self. Professionals need to know that there is potential for mismatching between emotional experience and facial expression, that autistic women have sensory needs (especially in pregnancy). Professionals frequently struggle to effectively take the needs and perspectives of autistic mothers into account, resulting in profoundly negative consequences for the mother.